Interactive Media to Explore Local Wisdom in Learning BIPA Distance at the Indonesian Embassy in Bern, Switzerland - Octo Dendy Andriyanto; Meilita Hardika; Sukarman Sukarman; Pensri Panich (AL-ISHLAH: Jurnal Pendidikan, 2023)
Media selection is needed to teach Bahasa Indonesia bagi Penutur Asing (BIPA) through distance learning (PJJ) to explore Indonesian local wisdom. BIPA learning problems often arise so that students cannot absorb the material optimally. BIPA learning in PJJ requires special attention because it is carried out online. The ability to apply information technology, especially when choosing learning media, is an important concern in BIPA learning. The focus of the discussion of this article includes 1) the BIPA class learning process at the Indonesian Embassy in Bern, Switzerland, and 2) Interactive media used in BIPA learning at the Indonesian Embassy in Bern, Switzerland. The method for this study uses a qualitative design by observing the distance learning process of BIPA at the Indonesian Embassy in Bern. The results of observations from the BIPA PJJ learning process at the Indonesian Embassy in Bern are that students have different backgrounds and basic abilities, and the use of interactive media is very effective in this learning. The media used include 1) word wall for learning vocabulary and grammar, 2) learning app pages for learning listening, reading, and grammar, and 3) a jam board for learning to write.